Youth and post-conflict reconstruction : agents of change - Schwartz, Stephanie (Washington, D.C. : United States Institute of Peace Press, 2010)
"A very welcome addition to the literature on youth and violence. Schwartz forcefully argues that we need to pay attention to the positive roles that youth may play in post-conflict reconstruction. Most importantly, she identifies and discusses strategies that may contribute to breaking the cycle of violence. This book will help change the perception of youth as primarily being a threat to one of youth representing an opportunity."--Henrik Urdal, The International Peace Research Institute, Oslo (PRIO).
In the post-conflict population, youth constitute a reservoir brimming with energy, ready to be channeled for good or ill. What causes some young people to return to fighting while others choose to work for a better future? Youth in Post-Conflict Reconstruction: Agents of Change uses three cases of post-conflict reconstruction--Mozambique, the Democratic Republic of the Congo, and Kosovo--to explore how youth affect the post-conflict reconstruction process and how domestic policy, NGO programming, international interventions, and cultural contexts may change that role. The hypotheses drawn from these comparisons will be useful both in guiding future research on youth's role in post-conflict reconstruction and in helping reconstruction actors facilitate the youth population's transition from war to peace. --Book Jacket.
Youth and post-conflict reconstruction : an analytical framework -- Mozambique : the "poster child" for reconstruction -- Democratic Republic of Congo : youth and the perpetuation of conflict -- Kosovo : youth as agents of change in an unstable environment -- Cross-case analysis and implications for future research.
Includes bibliographical references (pages 197-207) and index.
Keywords: Youth and war; Youth and peace; Youth in development; Postwar reconstruction -- Social aspects; Youth and peace; Youth and war; Youth in development; Jugend